2017
DOI: 10.11604/pamj.2017.27.259.11883
|View full text |Cite
|
Sign up to set email alerts
|

Hormone�-receptor expression status of epithelial ovarian cancer in Ibadan, South-western Nigeria

Abstract: IntroductionEpidemiological evidence strongly suggests that steroid hormones are implicated in the pathogenesis of ovarian cancer. Estrogen receptor (ER) and Progesterone receptor (PR) are prognostic indicators for a number of epithelial tumors and may play the same role in ovarian cancers. This study aims to evaluate the expression of ER and PR in epithelial ovarian cancer (EOC) in an African population and compare it with other prognostic factors such as age, International Federation of Gynaecology and Obste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…It has been suggested that these histotypes may respond to hormonal therapy [ 38 40 ]. The percentage of ER+ cases we observed (10.6%) is consistent with a recent OTTA study, which found that 16% of MOC had strong ER expression [ 37 ], but others report rates as low as 4% up to 19% [ 41 44 ]. None of the MOC cases in our cohort appear to have received hormonal therapy, hence hormonal response data within this cohort is unknown.…”
Section: Discussionsupporting
confidence: 92%
“…It has been suggested that these histotypes may respond to hormonal therapy [ 38 40 ]. The percentage of ER+ cases we observed (10.6%) is consistent with a recent OTTA study, which found that 16% of MOC had strong ER expression [ 37 ], but others report rates as low as 4% up to 19% [ 41 44 ]. None of the MOC cases in our cohort appear to have received hormonal therapy, hence hormonal response data within this cohort is unknown.…”
Section: Discussionsupporting
confidence: 92%
“…Gonadotropins, estrogens, and androgens may promote ovarian cancer progression, whereas gonadotropinreleasing hormone and progesterone may protect against ovarian cancer (8,28,29). Empirical studies have corroborated that hormone receptors are expressed in both normal and ovarian cancer surface epithelium (30) and they may be associated with carcinogens and result in ovarian cancer (31,32). Although clinical trials using hormonal therapeutic agents in patients with ovarian cancer have been conducted (33, 34), their results have been inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Sex steroids play an important role in OVC development and progression (Gómora et al 2018 ). There is an elevated level of ER expression in epithelial ovarian cancer cells compared to benign and normal ovarian epithelial cells (Ajani et al 2017 ). Estrogen consumption, either as an oral contraceptive or hormone replacement therapy, increases the risk of OVC.…”
Section: Ovarian Cancermentioning
confidence: 99%